Political influencers on social media: language used and content of communication strategy of Indonesian politicians’ twitter accounts - Gatut Priyowidodo,; Ido Prijana Hadi,; Jandy E. Luik,; Inri Inggrit Indrayani, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Technology plays an essential role in all the worldwide media industries. Developments in the field of media have led to the existence of new mediums in communication. New mediums through mass media channels have given the public many options, including politicians, to share. This study examined how the language used by politicians and communication strategies through selected mediums influence society in the face of elections. This study focused on the messages conveyed through social media, namely Twitter. The study used a content analysis method that examined as many as six Twitter accounts of influential politicians in the community in Indonesia. The review period for selected Twitter accounts is from 10 September 2022 until 20 November 2022. The findings found that most Twitter account owners chose social and economic issues to write on Twitter accounts rather than political issues. This differs from the previous study’s results; most researchers stated that most politicians prioritize politics-related issues. This difference may be due to differences in terms of cultural, economic background, and political trends. While the language used is more of a common language, i.e., informal, than formal or provocative. The choice of language, neither formal nor "Layman language," makes what is presented accessible for the community to understand from different backgrounds. This means that politicians are making social media a medium for dealing with issues related to political matters.